Accountability Analysis of the Performance of the Regional Development Planning Agency (BAPPEDA) of Muara Enim Regency, Indonesia - Abdul Nadjib; Oemar Madri Bafadhal (Budapest International Research and Critics University, 2021)
This study aims to determine the performance accountability of the Regional Development Planning Agency (BAPPEDA) of Muara Enim Regency in 2017, including supporting factors and inhibiting factors. Accountability for the performance of regional apparatus is needed to measure the level of success and or failure of regional apparatus in achieving common goals and targets according to the performance targets set in the district RPJMD. This research was conducted with a qualitative approach and using descriptive analysis. The data collection technique used interview, observation, and documentation methods. The results showed that the performance accountability of BAPPEDA Muara Enim Regency in 2017 was very good, which was shown by the existence of excellent performance planning, performance measurement, performance reporting, internal evaluation, and performance achievements. The supporting factors for the performance of BAPPEDA in Muara Enim Regency are the existence of a strong team work, the development of achievement motivation, consistent monitoring and supervision of leaders and conducive organizational conditions that support the development of employee creativity and innovation. Meanwhile, the inhibiting factor felt by BAPPEDA employees was the absence of a special performance allowance for high workloads. This can lead to counter-productive and demotivating employees. It is recommended that in the future, consider the existence of a special performance allowance for the employees of BAPPEDA Muara Enim Regency and make BAPPEDA as a role model for performance development for other Regional Apparatus Organizations in Muara Enim Regency.